Reductions of Intergranular Corrosion Resistance and Wear Resistance in a Ni-Cr-Mo-Based Superalloy by Aging-Treatment-Induced Precipitation - Pengyan Zhang; Chi Zhang; Xiaoguang Zhou; Zhenyi Huang (Metals, 2021)
Ni-Cr-Mo-based superalloy is widely used as a key component in many critical environments. To ensure that the manufacturing process does not impact the long-term service performance of these components, the aging precipitation behavior at different temperatures and its effect on intergranular corrosion (IGC) resistance and wear resistance of a Ni-Cr-Mo-based C276 superalloy were investigated. The equilibrium phase diagram was calculated first using thermodynamic software to confirm the potential phases. Carbides of M6C were found to be formed at grain boundaries after aging at 800–850 °C for short-term treatment. The other two phases (μ phase and P phase) indicated in the phase diagram were not observed for the samples after aging treatment up to 15 h. Furthermore, double loop electrochemical potentiokinetic reactivation (DL-EPR) tests were conducted to examine the IGC resistance. The degree of sensitization increased with the aging time and severe corrosion was found to occur at grain boundaries. For the first time, the influence of aging treatment on the wear behavior of this superalloy has been specifically studied. Concerning the hot processing of Ni-Cr-Mo-based C276 superalloy, these results indicate the importance of avoiding high-temperature heat treatment for long periods.